Successful Treatment of Lung Calciphylaxis With Sodium Thiosulfate in a Patient With Sickle Cell Disease: A Case Report. Issue 6 (February 2016) - Arrestier, Romain; Dudreuilh, Caroline; Remy, Philippe; Boulahia, Ghada; Bentaarit, Bouteina; Leibler, Claire; Adedjouma, Amir; Kofman, Tomek; Matignon, Marie; Sahali, Dil; Dufresne, Roger; Deux, Jean-Francois; et al.
Abstract : Abstract: Calciphylaxis is a small vessel vasculopathy, characterized by medial wall calcification that develops in a few patients with chronic renal failure. The prognosis of skin calciphylaxis has improved considerably since the introduction of sodium thiosulfate (STS), but it remains unclear whether this therapy is effective against organ lesions related to calciphylaxis. Pulmonary calciphylaxis is a usually fatal medical condition that may occur in association with skin involvement in patients with end-stage renal disease. We report here the case of a 49-year-old woman homozygous sickle cell disease patient on chronic hemodialysis with biopsy-proven systemic calciphylaxis involving the lungs and skin. On admission, ulcerative skin lesions on the lower limbs and bilateral pulmonary infiltrates on chest computerized tomography scan were the main clinical and radiological findings. Skin and bronchial biopsies demonstrated calciphylaxis lesions. The intravenous administration of STS in association with cinacalcet for 8 consecutive months led to a clear improvement in skin lesions and thoracic lesions on chest computerized tomography scan. This case suggests for the first time that organ lesions related to calciphylaxis, and particularly lung injury, are potentially reversible. This improvement probably resulted from the combination of 3 interventions (more frequent dialysis, cinacalcet, and STS), rather than the administration of STS alone.